2015
DOI: 10.1589/jpts.27.3077
|View full text |Cite
|
Sign up to set email alerts
|

Does decrease of the thoracic kyphosis influence decrease knee adduction moment during gait? A preliminary study of a healthy population

Abstract: [Purpose] The purpose of this study was to investigate the influence of a decrease in thoracic kyphosis angle on the knee adduction moment during gait in healthy young individuals. [Subjects and Methods] Twenty-nine healthy adults, consisting of 15 males and 14 females (21.6 ± 1.1 years old), participated. The draw-in maneuver was used to decrease thoracic kyphosis, and thoracic kyphosis was measured using a SpinalMouse during normal standing and standing with the draw-in maneuver. The participants were requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The Nanba gait might decrease pelvic excursion, although this was not examined in the present study. The high trunk muscle activation might be similar to the draw-in maneuver gait, a gait that also reduces the KAM [ 34 ]. Regarding Gmed activation, Chang et al [ 35 ] reported that hip abduction weakness in the stance limb shifts the center of the body mass toward the swing limb, and this shift increases the KAM due to an increase in the lever arm length.…”
Section: Discussionmentioning
confidence: 99%
“…The Nanba gait might decrease pelvic excursion, although this was not examined in the present study. The high trunk muscle activation might be similar to the draw-in maneuver gait, a gait that also reduces the KAM [ 34 ]. Regarding Gmed activation, Chang et al [ 35 ] reported that hip abduction weakness in the stance limb shifts the center of the body mass toward the swing limb, and this shift increases the KAM due to an increase in the lever arm length.…”
Section: Discussionmentioning
confidence: 99%
“…A gait modification that requires no voluntary alignment change is the draw-in maneuver (DI), which is reported to improve thoracic kyphosis and reduce the KAM 17) . In the DI maneuver, participants are asked to bring their belly button up and toward the spine as they exhale, thereby contracting the abdominal muscles and increasing stability 18) .…”
Section: Introductionmentioning
confidence: 99%
“…In the DI maneuver, participants are asked to bring their belly button up and toward the spine as they exhale, thereby contracting the abdominal muscles and increasing stability 18) . Ota et al 17) reported that the KAM in a healthy population was significantly reduced by walking with a DI maneuver (DI gait) in which the thoracic kyphosis angle is decreased as measured in a standing position while performing the DI maneuver. The authors considered that insufficient instruction for the DI gait, i.e., a simple verbal command to "decrease the abdominal circumference", was a limitation of previous studies 17) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The external knee adduction moment (KAM) during walking is used as a surrogate for load on the knee joint 1 ) , and its association with knee osteoarthritis (OA) has been discussed in many previous studies 2 , 3 , 4 , 5 , 6 ) . Miyazaki et al examined the relationship between KAM at baseline and the progression of knee OA at a 6 year follow up in patients with medial compartment knee OA, and concluded that KAM could predict radiographic OA progression 7 ) .…”
Section: Introductionmentioning
confidence: 99%